2006
DOI: 10.1071/ea03188
|View full text |Cite
|
Sign up to set email alerts
|

Crude protein and amino acid composition of honey bee-collected pollen pellets from south-east Australia and a note on laboratory disparity

Abstract: Pollen pellets collected from honey bees foraging at 62 floral species were analysed for protein and amino acid content and their value for honey bee nutrition was determined. The crude protein levels of all pollen pellets analysed ranged from 9.2% for Hypochoeris radicata (flatweed) to 37.4% for Echium plantagineum (Paterson’s curse) with a mean of 25.9%. Pollen pellets from 15 species were identified as providing protein levels below those acknowledged to satisfy honey bee dietary requirements when they are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 6 publications
8
100
0
2
Order By: Relevance
“…The protein content of bee-collected sunflower pollen appears to be deficient and at the bottom of the range for the five major species. Data obtained in the present study confirm the findings of Somerville and Nicol (2006) in Australia, Pernal and Currie (2000) in Canada, Tasei and Aupinel (2008) in France, Nicolson and Human (2013) in South Africa who also found low protein content in bee-collected sunflower pollen. The protein level (18.14% DM) in bee-collected rape pollen was lower than that obtained by Pernal and Currie (2000) in Canada.…”
Section: Discussionsupporting
confidence: 81%
“…The protein content of bee-collected sunflower pollen appears to be deficient and at the bottom of the range for the five major species. Data obtained in the present study confirm the findings of Somerville and Nicol (2006) in Australia, Pernal and Currie (2000) in Canada, Tasei and Aupinel (2008) in France, Nicolson and Human (2013) in South Africa who also found low protein content in bee-collected sunflower pollen. The protein level (18.14% DM) in bee-collected rape pollen was lower than that obtained by Pernal and Currie (2000) in Canada.…”
Section: Discussionsupporting
confidence: 81%
“…Cappelari et al (2009) also reported that Africanized bees developed higher protein levels in the hemolymph than European bees fed the same diet, suggesting more efficient metabolism of ingested nutrients. In the field experiments, the high-protein diets also increased colony growth parameters during periods of scarcity of pollen resources, as also reported by Mattila and Otis (2006) and Somerville and Nicol (2006). Garcia et al (1986) supplied various protein foods with 20, 30 and 40% crude protein; they found that crude protein negatively influences food collection.…”
Section: Discussionsupporting
confidence: 59%
“…Low levels of total soluble and reducing sugars for pollen pellets of maize were observed. Higher protein contents, over 40%, were found in all four types of Egyptian pollen pellets, which were in agreement with the high protein content of 25.9% in bee pollen, produced in the Southeast of Australia (Somerville and Nicol, 2006). The greatest part of nitrogen content in pollen was in the protein fraction, this being the second most abundant group of nutrients, after the carbohydrates.…”
Section: General Chemical Analysissupporting
confidence: 67%
“…Therefore, proteins of pollen pellets were fractionated and investigated for their ratio. As stated by Somerville and Nicol (2006), the crude protein levels, of all pollen pellets analysed, ranged from 9.2% (Hypochoeris radicata) to 37.4% (Echium plantagineum), with a mean of 25.9%. Therefore, honey proteins could be used as chemical markers of the floral origin of honey (Baroni et al, 2002) or for higher levels of valuable minerals (Stanciu et al, 2011).…”
Section: General Chemical Analysismentioning
confidence: 99%